Trend Inflation, Wage Indexation, and Determinacy in the U.S. - Guido Ascari; Nicola Branzoli; Efrem Castelnuovo (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
We combine an estimated monetary policy rule featuring time-varying trend inflation and stochastic coefficients with a medium scale New Keynesian framework calibrated on the U.S. economy. We find the impact of variations in trend inflation on the likelihood of equilibrium determinacy to be both modest and limited to the second half of the 1970s. In contrast, our counterfactual exercises suggest that the change in the Federal Reserve's policy response to inflation is likely to have been the main driver leading the U.S. economy to a unique equilibrium during the Great Moderation. We highlight the impact of wage indexation on policymakers' ability to induce economic stability, and provide fresh evidence on the relationship between trend inflation, wage indexation and determinacy in the post-WWII U.S. economic environment. Further simulations show that rising the Federal Reserve's inflation target to four percent would be consistent with equilibrium uniqueness conditional on a policy as the one estimated on the U.S. post-1982 sample period.
Keywords: C22; E3; E43; E5; 330; Monetary Policy; Trend Inflation; Great Moderation; Determinacy; Wage indexation